An experimental study of thermal comfort and aerodynamic efficiency of recreational and racing bicycle helmets - Alam, F.; Chowdhury, H.; Elmir, Z.; Sayogo, A.; Love, J.; Subic, A. (Procedia Engineering, 2010)
The thermal comfort and aerodynamic efficiency are becoming important factors in bicycle helmet design and marketing. Currently most of the manufacturers primarily focus on safety features in helmet rather than aerodynamic efficiency and/or thermal comfort. The characteristics of the bicycle helmet (position, geometry and number of vents) are extremely important features for heat dissipation and aerodynamic drag. A comprehensive research is needed to improve the design of bicycle helmets. As part of a larger study, five commercially available helmets have been studied using RMIT Industrial Wind Tunnel under a range of wind speeds, yaw and pitch angles to determine their aerodynamic and thermal performance. In order to obtain the results as realistic as possible, an instrumented mannequin was used. Thermal comfort was measured based on heat dissipation properties of each helmet as a function of wind speeds. A relative ranking of each helmet was made based on their aerodynamic and thermal properties. Modification to one of the helmets indicates that there is scope for further improvements.